2014
DOI: 10.1128/mbio.02034-14
|View full text |Cite
|
Sign up to set email alerts
|

An Inner Membrane Cytochrome Required Only for Reduction of High Redox Potential Extracellular Electron Acceptors

Abstract: Dissimilatory metal-reducing bacteria, such as Geobacter sulfurreducens, transfer electrons beyond their outer membranes to Fe(III) and Mn(IV) oxides, heavy metals, and electrodes in electrochemical devices. In the environment, metal acceptors exist in multiple chelated and insoluble forms that span a range of redox potentials and offer different amounts of available energy. Despite this, metal-reducing bacteria have not been shown to alter their electron transfer strategies to take advantage of these energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
158
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(176 citation statements)
references
References 56 publications
9
158
0
1
Order By: Relevance
“…Moreover, the availability of specific Fe(III) phases may have important implications for the energetics of microbial iron reduction. A recent study shows that G. sulfurreducens operates multiple ironrelated respiratory pathways depending on the redox potential of the substrate being reduced (67). In this case, as the crystallinity of the ferric substrates increases, the amount of energy generated by their reduction decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the availability of specific Fe(III) phases may have important implications for the energetics of microbial iron reduction. A recent study shows that G. sulfurreducens operates multiple ironrelated respiratory pathways depending on the redox potential of the substrate being reduced (67). In this case, as the crystallinity of the ferric substrates increases, the amount of energy generated by their reduction decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Detected changes of electron conduit using voltammetry and measured NAD(P)H level did not give clear information on these processes (Li et al, ; Marsili, Sun, & Bond, ; Rose & Regan, ; Song et al, ; Yoho, Popat, & Torres, ; Zhu et al, ). Recently, the cytoplasmic CbcL and ImcH are recognized as an electron relay when polarizing the cells at less than or equal to −0.1 V and higher potentials, respectively (Levar et al, , ; Zacharoff et al, ). However, this finding is not sufficient to elucidate the metabolism and redox conduction behaviors of G. sulfurreducens biofilms at different potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Another major variable in the EAB cultivation and operation is the electrode potential. The applied potential has been reported to have an impact on microbial EET pathways, e. g., via the activation of low or high potential electron transfer pathways . In some cases more positive anode potentials proved to be advantageous to achieve higher current densities, whereas other studies reported detrimental effects of too high anode potentials, e. g., due to increasing redox stress, and thus recommended the use of less positive potentials .…”
Section: Introductionmentioning
confidence: 99%